2016
DOI: 10.18001/trs.2.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Secondhand E-cigarette Aerosol among Twitter Users

Abstract: Objectives There is considerable debate among the public health community about the health risks of secondhand exposure to the aerosol from electronic cigarettes (e-cigarettes). Despite mounting scientific evidence on the chemical content of e-cigarette aerosol, public perceptions of the relative safety of secondhand e-cigarette aerosol have not been well characterized. Method This study collected tweets, or messages sent using Twitter, about exposure to secondhand e-cigarette aerosol over a 6-week period in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Social media users tend to include multiple hashtags within their posts, which resulted in duplicate tweets being collected. Duplicate tweets within keyword corpora for each year and across keyword corpora from the co-use of hashtags were removed, resulting in the inclusion of only unique tweets [ 31 ]. Data were assigned a number in ascending order and 100 tweets from each keyword corpus for each year were randomly selected for analysis, using an online random sequence generator [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Social media users tend to include multiple hashtags within their posts, which resulted in duplicate tweets being collected. Duplicate tweets within keyword corpora for each year and across keyword corpora from the co-use of hashtags were removed, resulting in the inclusion of only unique tweets [ 31 ]. Data were assigned a number in ascending order and 100 tweets from each keyword corpus for each year were randomly selected for analysis, using an online random sequence generator [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…First, the definition of a health-promoting message was a message that included both health behaviors and health outcomes [ 15 ], so we excluded some messages, such as messages only referring to the cause of a disease. Second, in a health topic, the amount of social content was often much larger than the amount of health professional content [ 61 ]. Third, we found that the celebrity effect exists in Weibo health themes.…”
Section: Discussionmentioning
confidence: 99%
“…Social media research on e-cigarettes has focused on using data from Twitter, with recent studies examining perception, 9 awareness 3031 and advertising. 1014 While sites such as Twitter were created before the ubiquitous use of smartphones, Instagram originated as a smartphone app, with features that rely on mobile devices that can take high-quality photos and have fast internet connections; when combined with vaping activities (eg, cloud chasing) that are best suited for real-time capture and sharing, it makes Instagram an ideal platform for e-cigarette users and provides ample data for researchers to explore.…”
Section: Discussionmentioning
confidence: 99%
“…910 However, Instagram—a social networking site focused on picture-based content—has been underused for these purposes. 11 Instagram allows users to capture and customise photos to share online.…”
Section: Introductionmentioning
confidence: 99%